Revisiting 1948 Insurgencies and the Cold War in Southeast Asia - Richard Mason (Kajian Malaysia, 2009)
In 1948 left-winged insurgencies broke out in Malaya, Burma, Indonesia and the Philippines. These insurgencies continued to leave their imprint on the region today. The papers in this volume discuss the significance of these insurgencies in the course of Southeast Asian history, with particular reference to the Cold War in the region. These papers are part of a larger collection that were presented at a Roundtable on the Sixtieth Anniversary of 1948: Reassessing the Origins of the Cold War in Southeast Asia, organised by the Asia Research Institute, National University of Singapore, 10?11 July 2008. The central concern of the Roundtable was to discuss the significance of 1948 in Southeast Asian history and to determine “in what way 1948 was – or perhaps was not – ‘the beginning of the Cold War’ in Southeast Asia.” Were the seemingly simultaneous left-winged insurgencies that broke out in the region in 1948 Soviet-directed as part of the Cold war in Asia or did the insurgencies emerged from local circumstances affecting the strategies of the struggles of these left-wings movements in the respective counties concerned? How important were the insurgencies in affecting the course of Southeast Asian history? Did 1948 constitute a watershed in Southeast Asian history? The papers in this volume address these issues among many others.